Evaluation of the environmental sustainability of the inshore great scallop (Pecten maximus) fishery in Galicia. (16th May 2021) - Cortés, Antonio; González‐García, Sara; Franco‐Uría, Amaya; Moreira, Maria Teresa; Feijoo, Gumersindo
Abstract: Great scallop ( Pecten maximus ) is a bivalve species belonging to the Pectinidae family that is deeply linked to the well‐known network of pilgrimages in Spain (The Way of Saint James), becoming a gourmet product of the Galician cuisine. The goal of this study was to fill the gaps that currently exist in a specific inventory dedicated to the capture and processing of great scallop, as well as to assess the environmental burdens derived from this system. The construction of a comprehensive life cycle inventory was one of the fundamental stages, gathering primary information from questionnaires filled out by 14 skippers and the manager of the evisceration plant in the port of Cambados. Diesel consumption of the fishing boats was identified as the major contributor to the environmental burdens. Furthermore, electricity consumption in the evisceration plant also stood out as a determinant element in the environmental profile of the product. The integrated GHG emission/protein content correlation placed the scallop in the quadrant of high‐protein content (the highest of the fisheries), but also high environmental impact (mainly due to the high fuel use intensity and low edible yield). It is important to highlight that to date and according to our knowledge, this is the first study that aims to analyze the environmental impacts of the great scallop fishery.